A Very Rare Cause of Thrombotic Peripheral Occlusion - Kretzschmar, Daniel; Thieme, Marcus; Aschenbach, Rene; Schulze, P. Christian; Möbius-Winkler, Sven (International Journal of Angiology, 2022)
A 45-year-old healthy woman presented with claudication of the right leg. The resting ankle-brachial index (ABI) was reduced to 0.6, and a duplex scan revealed an occlusion of the right popliteal artery. Angiography presented a patent superficial femoral artery that ends above the knee joint. Laterally, there was delayed retrograde contrast filling of the popliteal artery. After exploring the internal iliac artery, we crossed a thrombotic occlusion of a persisting sciatic artery (PSA). Local thrombolysis with recombinant tissue plasminogen activator (1 mg/h) was initiated. The Angiography 18 hours later showed a reduction of thrombotic material and relevant stenosis in the proximal part of the vessel. Residual thrombus and the stenosis were covered by two stentgrafts (Gore Viabahn Endoprosthesis) that were stabilized by an interwoven stent (Supera). Final angiography displayed a patent sciatic artery and a three-vessel run off. Postinterventional ABI was normalized to 1.0. The magnetic resonance imaging 6 days after the intervention demonstrated a patent PSA again and a normal blood flow on the left leg. A PSA should be included in the differential diagnosis of lower limb ischemia or suspected aneurysm formation. We demonstrated the feasibility of an interventional approach with an excellent outcome in this case.
Keywords: acute limb ischemia; thrombotic occlusion; persisting sciatic artery; thrombolysis; stentgraft; interwoven stent